Islamic Education Financing Models - Alif Basman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Educational administrators need to comprehend various models of educational funding as a guide in executing educational programs. The selection of funding models will impact the policies implemented by the administrators. When administrators exercise wisdom in selecting the appropriate funding model, it will influence the policies adopted and strategic steps taken in educational development. The method employed in this writing is a literature study (library research). The research conducted reveals that there are several models such as the Flat Grant Model, Foundation Plan Model, Guaranteed Tax Base Plan Model, Percentage Equalizing Model, Power Equalizing Plan Model, Full State Funding Model, Resource Cost Model, Choice and Voucher Plans Model, and Weight Student Plan Model, each with its distinct characteristics and impacts in allocating educational funds.